Comparative Analysis Of AI And Human Translations Of Qur’anic Legal Verses In Surah Al-Ma’idah - Abdalhussein, Hussein Fahim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Translation of Qur'anic legal verses, mainly from Surah Al-Mā'idah, poses significant challenges due to its complex legal, theological, and cultural context. This study aims to evaluate the accuracy and effectiveness of AI compared to human translation of these verses, highlighting the challenges faced in translating these complex texts into English. Utilizing Rosa's (2010) Approach to Descriptive Translation Studies, this study identifies contextual norms and influences on translation decisions, providing a framework for comparing translation strategies used by AI and human translators. The study adopts a qualitative design, analyzing ten purposefully selected verses from Surah Al-Mā'idah, translated by AI (ChatGPT) and Abdullah Yusuf Ali. This comparative analysis illustrates the strengths and weaknesses of AI and human translation in capturing the detailed nuances of Qur'anic legal verses. Findings indicate that AI translations demonstrate speed and consistency but lack the depth needed to convey theological and legal subtleties accurately. Human translations, on the other hand, exhibit more significant variability. However, they are more adept at reflecting the complex contextual meanings inherent in the original text. These results are of great importance for translation studies, particularly in understanding the capabilities and limitations of AI in translating complex religious texts. The translation of the legal verses of the Qur'an, especially from Surah Al-Mā'idah, poses significant challenges due to its complex legal, theological, and cultural context. The implications of the current study extend to scholars, translators, and religious educators who aim to improve the quality and reliability of Qur'an translations for diverse audiences. This contribution is significant in bridging the gap between traditional translation methods and emerging digital technologies in translating religious texts.